2019
DOI: 10.3390/genes10090725
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptome Analysis Identifies Biological Pathways and Candidate Genes for Feed Efficiency in DLY Pigs

Abstract: Feed cost accounts for approximately 65–75% of overall commercial pork production costs. Therefore, improving the feed efficiency of pig production is important. In this study, 12 individuals with either extremely high (HE) or low (LE) feed efficiency were selected from 225 Duroc × (Landrace × Yorkshire) (DLY) pigs. After the pigs were slaughtered, we collected small intestine mucosal tissue. Next, RNA sequencing (RNA-seq) analysis was used to reveal the presence and quantity of genes expressed between these e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Approaches to resolve the porcine immune cell landscape at the transcriptional level have also been employed; however, traditional bulk RNA sequencing (RNA-seq) or microarray approaches fail to provide cellular resolution needed to decode such a complex cellular community (Herrera-Uribe et al, 2021), especially when immunoreagents for sorting of cells into more homogenous populations are lacking. Numerous studies have assessed transcriptional dynamics in the porcine intestinal tract but did not attempt to deconvolute cells into specific populations, a critical step in understanding functions of specific cells (Wang et al, 2008(Wang et al, , 2019aFreeman et al, 2012;Mach et al, 2014;Zhu et al, 2014;Inoue et al, 2015;Tan et al, 2017;Maroilley et al, 2018;Beiki et al, 2019;Meng et al, 2020;Summers et al, 2020;Jin et al, 2021;Pan et al, 2021). Some bulk RNA-seq studies have sorted porcine immune cells into specific populations based on cell surface markers but primarily focused on studying cells from the periphery and non-intestinal tissues (Auray et al, 2016(Auray et al, , 2020Foissac et al, 2019;Herrera-Uribe et al, 2021;Kim et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Approaches to resolve the porcine immune cell landscape at the transcriptional level have also been employed; however, traditional bulk RNA sequencing (RNA-seq) or microarray approaches fail to provide cellular resolution needed to decode such a complex cellular community (Herrera-Uribe et al, 2021), especially when immunoreagents for sorting of cells into more homogenous populations are lacking. Numerous studies have assessed transcriptional dynamics in the porcine intestinal tract but did not attempt to deconvolute cells into specific populations, a critical step in understanding functions of specific cells (Wang et al, 2008(Wang et al, , 2019aFreeman et al, 2012;Mach et al, 2014;Zhu et al, 2014;Inoue et al, 2015;Tan et al, 2017;Maroilley et al, 2018;Beiki et al, 2019;Meng et al, 2020;Summers et al, 2020;Jin et al, 2021;Pan et al, 2021). Some bulk RNA-seq studies have sorted porcine immune cells into specific populations based on cell surface markers but primarily focused on studying cells from the periphery and non-intestinal tissues (Auray et al, 2016(Auray et al, , 2020Foissac et al, 2019;Herrera-Uribe et al, 2021;Kim et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…According to the data from the United States Department of Agriculture (USDA), China produces more than 650 million pigs per year, which represents more than 50% of the global pig production. The most popular commercial pig breed in China, as well as in the world, is Duroc × (Landrace × Yorkshire) (DLY) crossbred pigs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The total of all RNA transcripts occurring in the organism, both coding and non-coding, is recorded. Some research groups have already used the transcriptome level to study feed efficiency in pigs [ 88 , 89 , 90 , 91 , 92 ]. All of these studies showed that the transcriptomic method is a powerful tool to gain a deeper insight into the genetic differences between efficient and less efficient animals.…”
Section: Conclusion and Perspectivementioning
confidence: 99%